Cryogenic treatments on AISI 420 stainless steel: Microstructure and mechanical properties. - Prieto, Germán (2014)
Cryogenic treatments have been employed over the last three decades in both tool and high-alloy steels to improve wear resistance, mainly through the transformation of retained austenite and the precipitation of fine carbides. The application of these treatments to low-alloy steels and even to non-ferrous materials is becoming the subject of several investigations, due to their potentiality to reduce wear. This study was aimed at analyzing the microstructural changes and the effect of cryogenic treatments on hardness and impact toughness in martensitic AISI 420 stainless steel. X-ray diffraction (XRD) was employed for phase analysis and characterization, while carbide volume fraction, size and composition evaluation was measured by using scanning electron microscopy (SEM-EDX) and Energy Dispersive Spectrometry (EDS). Hardness was assessed with Vickers technique and the impact toughness was measured by means of Charpy׳s V-notch tests. Fracture surfaces were analyzed by scanning electron microscopy to evaluate the fracture micromechanisms. In this study, it has been experimentally demonstrated that cryogenic treatments favors the precipitation of small carbides, which also present a more homogeneous size distribution. It was observed that this microstructural feature is responsible for the improvement in the mechanical properties of the material.